2014
DOI: 10.1038/gim.2014.41
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors affecting statin concentrations and subsequent myopathy: a HuGENet systematic review

Abstract: Statins, 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase inhibitors, have proven efficacy in both lowering low-density-lipoprotein levels and preventing major coronary events, making them one of the most commonly prescribed drugs in the United States. Statins exhibit a class-wide side effect of muscle toxicity and weakness, which has led regulators to impose both dosage limitations and a recall. This review focuses on the best-characterized genetic factors associated with increased statin muscle concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 72 publications
1
66
1
1
Order By: Relevance
“…14 Furthermore, a large systematic review of genetic factors that could influence statin-associated muscle symptoms showed that African Americans have different genetic variants of cytochrome P450 enzymes and influx transporter SLCO1B1 that may affect statin concentrations and subsequent statin-associated muscle symptoms. 15 In fact, in our study, lower BMI was associated with muscle symptoms only in non-African Americans but not African-Americans, and African Americans have lower percentage of the SLCO1B1 TC genotype compared to non-African Americans. Given a small sample size of our study, we may not be detecting independent increased risk of muscle symptoms in African Americans.…”
Section: Discussioncontrasting
confidence: 44%
“…14 Furthermore, a large systematic review of genetic factors that could influence statin-associated muscle symptoms showed that African Americans have different genetic variants of cytochrome P450 enzymes and influx transporter SLCO1B1 that may affect statin concentrations and subsequent statin-associated muscle symptoms. 15 In fact, in our study, lower BMI was associated with muscle symptoms only in non-African Americans but not African-Americans, and African Americans have lower percentage of the SLCO1B1 TC genotype compared to non-African Americans. Given a small sample size of our study, we may not be detecting independent increased risk of muscle symptoms in African Americans.…”
Section: Discussioncontrasting
confidence: 44%
“…Another theory surrounds the role of the multiple drug protein-2 (a membrane transport protein from the ABC superfamily excreting toxins into bile), since simvastatin is a substrate of this transporter 15. Finally, there are several genetic factors that may also predispose one to statin-related toxicity16 or genetic mutations (eg, involving CYP2C8) which may be relevant in a statin–ciprofloxacin interaction 5…”
Section: Discussionmentioning
confidence: 99%
“…In our datasets, COMT should not be relied upon as a PGx marker. In contrast, it should be noted that many of the well-known genes associated with drug response were adequately covered for genotype analysis: CYP2D6 (tamoxifen) [19,20], CYP2C19 (clopidogrel) [21,22], SLCO1B1 (statins) [23,24] (data not shown).…”
Section: Discussionmentioning
confidence: 99%